Optimization of Processing Parameters for Particle Filtration Efficiency of Polypropylene Melt-blown Fabric - Jiang, Taijun (Fibers Polym, 2021)
Polypropylene melt-blown fabric as the core filter materials plays an important role in manufacturing civil and medical epidemic prevention products. The aim of this study was to optimize and control the particle filtration efficiency and apparent surface quality of the melt-blown fabric from the perspectives of electret masterbatch composition and processing parameters. Magnesium stearate and fumed silica were used as the electret to manufacture polypropylene melt-blown fabric. The layout and charge voltage of the electret device was taken as the variables to optimize and improve the particle filtration efficiency and bulkiness coefficient of the fabric. The temperature of the barrel and die was controlled to enhance the surface quality and corresponding particle filtration efficiency. The results showed that a combination of organic magnesium stearate and inorganic fumed silica could obtain a balance between particle filtration efficiency and smooth processing without being jammed. Increasing the charge voltage and rearranging the position of the charge wires could significantly enhance the particle filtration efficiency. A better particle filtration efficiency and reasonable bulkiness coefficient could be obtained by controlling the diameter of the filaments by regulating the temperature of the barrel and die as well as the suction intensity. The results obtained from this study can offer valuable references in optimization of electret master batch formulation and processing parameters for melt-blown fabric production with different resin.